Global Jihad and Local Sentiment: The Impact of the Hamas-Israel Conflict on Radicalization in Indonesia - Eneng Ervi Siti Zahroh Zidni; Muhammad Luthfi Zuhdi; Yon Machmudi; Muhamad Syauqillah (Green Publisher Indonesia, 2024)
The prolonged conflict between Hamas and Israel has significant impacts on the social and political dynamics in various countries, including Indonesia. This study aims to analyze how this conflict affects radicalization and the development of terrorism ideology in Indonesia. The methodology employed is a qualitative approach based on narrative analysis through document studies and secondary data. This research applies the Relative Deprivation Theory to explain the dissatisfaction felt by Indonesian Muslims regarding the conditions in Palestine, and the Framing Theory to understand how the conflict narrative is framed by radical groups. The findings indicate that the narrative of Palestinian suffering and the legitimacy of jihad are used by extremist groups to recruit new members and garner support. Additionally, this phenomenon contributes to an increase in anti-Israel sentiment among Indonesian society. The findings reveal the complex relationship between international conflicts and local radicalization, which calls for more serious attention from the government in addressing potential terrorism threats arising from these sentiments.